New anticoagulant drugs - Marinko, Marija; Novakovic, Aleksandra; Divac, Tatjana; Milojevic, Predrag; Nenezić, Dragoslav (Medicinski časopis, 2012)
Anticoagulants are effective agents for the prevention and treatment of thrombosis and thromboembolic complications, which represent a common cause of morbidity and mortality. Despite a clinical efficiency, traditional anticoagulants are all associated with significant drawbacks. As a result, modulation of the coagulation process represents important target in the development of new oral and parenteral anticoagulants today. The new oral anticoagulants selectively target thrombin (ximelagatran, dabigatran etexilate) or factor Xa (rivaroxaban, apixaban, edoxaban). Unlike traditional anticoagulants, these drugs have rapid onset of action and a relatively wide therapeutic range, do not require routine coagulation monitoring and have low potential for food and drug interaction. Although the need for new oral anticoagulants exceeds the need for parenteral anticoagulants, a series of new potentially useful parenteral anticoagulants are in different stages of development. The new parenteral anticoagulants achieve their effects through indirect (semuloparin, idrabiotaparinux) or direct inhibition of factor Xa (otamixaban), as well as through inhibition of coagulation factor IXa (RB006). The main characteristics of these agents are a rapid onset of action and a predictable anticoagulant effect, whereby the most of them can be rapidly neutralized by adequate antidote.